Evaluation on consumers' preferences in purchasing cooking edible palm oil in Kampung Changkat / Siti Nadiah Abdullah - Abdullah, Siti Nadiah (Faculty of Plantation and Agrotechnology, 2016)
Usage of palm oil in various products is around 80% of major applications to edible oil produced while 20% is produced for non-edible oil growing (Basiron, 2004). The consumers' preference plays an important role in any business where the consumer's demand for goods such edible palm oil. This study was conducted at Kampung Changkat, Nibong Tebal, Pulau Pinang and the total of sample is 234 taken from 600 population determined by "simple random sampling method" . This study is done by using the questionnaire to distribute to respondent and the result was analyze with use factor analysis an cross tab chi-square analysis. The survey was decided to do here because to know either this factor such as healthy, quality, satisfaction value, eco-friendly, price, and knowledge factor are relevant to preference in purchasing cooking edible palm oil, especially in Pulau Pinang. Based on the result, as a suggestion for future, the producer should take part in improving their product (cooking edible palm oil) to fulfilled the consumers' preferences.